Synthesis And Characterization Of Mesoporous Carbonated Hydroxyapatite For Drug Delivery Application - Mohammad, Nur Farahiyah (2017)
Mesoporous hydroxyapatite (HA) as a drug carrier has been widely studied but seldom focused was given on more biocompatible species for example mesoporous carbonated hydroxyapatite (CHA). Incorporation of mesoporous structure is expected to give the CHA better biocompatibility properties and drug release profile. The ultimate aim of this research is to synthesise mesoporous CHA that demonstrates optimum pore characteristics for drug delivery application and to investigate the biocompatibility properties of the material. The effects of different type of surfactant with different numbers of polyethylene oxide-polypropylene oxide (PEO-PPO) units, types of washing solvents used (such as deionized water, ethanol and acetone), concentrations of surfactant and concentration of carbonate precursor on the pore characteristics of the mesoporous CHA were investigated. Mesoporous CHA was synthesised by hydrothermal method using non-ionic triblock co-polymers surfactant as a template to introduce pores within CHA particles. Among different washing solvents studied, deionized water is more preferable as a solvent for the washing process, as it is not only physiologically biocompatible than ethanol but also resulted a higher surface area (63 m2g-1) compare to other solvents. Mesoporous CHA synthesise using P123 (63 m2g-1) has a larger surface area than those produced using F127 (58 m2g-1). The transmission electron microscope images confirmed the presence of mesopores as an array of pore channels in the synthesised sample. The optimum pore characteristics (i.e. surface area = 78 m2g-1, pore size = 27 nm and pore volume = 0.542 nm) of mesoporous CHA was obtained when surfactant concentration (1.7 mM) was maintained closed to critical micelle concentration (CMC), 0.0044 mM. High carbonate precursor concentration (1 M) was found to produce mesoporous CHA with high surface area and carbonate content within the range of natural human bone (2−8%). The biocompatibility of the materials was determined by carrying out the in vitro bioactivity study, cytotoxicity and alkaline phosphatase (ALP) tests on the mesoporous CHA. The in vitro bioactivity, cytotoxicity and ALP tests results proved that the mesoporous CHA has a good biocompatibility comparable to commercial HA. Mesoporous CHA was confirmed non-toxic to the MC3T3-E1 cells. The material also supported cells differentiation at various concentration extracts up to 25 mg/ml. Finally, drug loading and release profile of the mesoporous CHA were evaluated using ibuprofen and cisplatin as models drug. As for investigation using ibuprofen, the mesopores introduced within the CHA structure has enabled it to have higher drug loading capacity (DLC = 18.9 wt%) and better loading efficiency (28 wt%) as well as higher release amount (about 39 %) than nonporous CHA (DLC = 6.6 wt%, EE = 13.2 wt%, release amount about 10%). Mesoporous CHA with larger surface area demonstrated better controlledrelease property than the lower surface area mesoporous CHA.